1987
DOI: 10.1159/000118653
|View full text |Cite
|
Sign up to set email alerts
|

Afferents of the Frontal Cortex in the Echidna (<i>Tachyglossus aculeatu</i><i>s</i>). Indication of an Outstandingly Large Prefontal Area

Abstract: Afferents of the large, electrically 'silent' frontal cortex in an egg-laying mammal, the echidna, were studied with the somatopetal axonal transport technique. This cortical area receives thalamic projections only from the anterior part of the antero-mediodorsal region. The medial parts of the cortex receive afferents from more medial neurons, whereas the lateral area is innervated from the laterally placed perikarya of this thalamic region. The nonthalamic afferents to the frontal cortex are, with few except… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 37 publications
1
16
0
Order By: Relevance
“…Divac et al [1987] had been unable to identify a claustrum in the echidna brain in Nissl stained material and did not find any retrogradely labeled cells in the region following injections into the frontal cortex. More recently, Butler et al [2002] re-examined this issue in both echidna and platypus brain and concluded that there was no cytoarchitectonically distinct claustrum in either brain.…”
Section: Developmental and Evolutionary Significance Of The Presence mentioning
confidence: 96%
See 2 more Smart Citations
“…Divac et al [1987] had been unable to identify a claustrum in the echidna brain in Nissl stained material and did not find any retrogradely labeled cells in the region following injections into the frontal cortex. More recently, Butler et al [2002] re-examined this issue in both echidna and platypus brain and concluded that there was no cytoarchitectonically distinct claustrum in either brain.…”
Section: Developmental and Evolutionary Significance Of The Presence mentioning
confidence: 96%
“…Their figure 3 shows only a small, medial portion of an anterior part of the piriform lobe, although a pale region in the top edge of their figure 3D may represent the rostral part of insular claustrum. Thirdly, the unusual white matter topography of monotremes, due mainly to the large anterior commissure and its attendant commissural fiber bundles, may have made the identification of the insular claustrum difficult for previous authors [Divac et al, 1987;Butler et al, 2002]. The putative insular claustrum in the echidna is embedded in commissural fiber bundles approaching and leaving the anterior commissure.…”
Section: Developmental and Evolutionary Significance Of The Presence mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the human 'record' of 33% of the neocortical area occupied by the prefrontal cortical area, is well surpassed by an egg-laying mammal (the echidna, Tachyglossus aculeatus), for which the corresponding figure is 50% (e.g. Divac et al 1987). Also, birds lack a neocortex as a distinct brain area but they show convincing signs of pain, for example, selecting feed with pain killers under circumstances that would be experienced as painful by humans (Gentle 1992, Danbury et al 2000).…”
Section: Physiological Indications Of Sentience In Fishesmentioning
confidence: 99%
“…Many aspects of echidna neurobiologye.g. their high degree of cortical gyrification, enlarged pre frontal cortex, and apparent absence of SI1 [Pirlot and Nel son, 1978;Divac et al, 1987; Krubitzeret a!., 1995] -point to a peculiar, yet highly advanced central nervous system organisation. Indeed, the proportion of brain volume occu pied by the cerebral cortex in Tachyglossus (43%) is similar to that in eutheria mammals such as prosimians (54%) [Pir lot and Nelson, 1978].…”
Section: Introductionmentioning
confidence: 99%